2008
DOI: 10.1073/pnas.0806748105
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead Box m1 transcription factor is required for perinatal lung function

Abstract: The Forkhead Box m1 (Foxm1 or Foxm1b) transcription factor (previously called HFH-11B, Trident, Win, or MPP2) is an important positive regulator of DNA replication and mitosis in a variety of cell types. Global deletion of Foxm1 in Foxm1 ؊/؊ mice is lethal in the embryonic period, causing multiple abnormalities in the liver, heart, lung, and blood vessels. In the present study, Foxm1 was deleted conditionally in the respiratory epithelium (epFoxm1 ؊/؊ ). Surprisingly, deletion of Foxm1 did not alter lung growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
115
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(123 citation statements)
references
References 24 publications
(51 reference statements)
3
115
0
2
Order By: Relevance
“…CMV-Renilla was used as an internal control to normalize transfection efficiency. A dual luciferase assay (Promega) was performed 24 h after transfection as described previously (38).…”
Section: Cloning Of the Mouse 11␤-hsd2 Promoter Region And Luciferasementioning
confidence: 99%
“…CMV-Renilla was used as an internal control to normalize transfection efficiency. A dual luciferase assay (Promega) was performed 24 h after transfection as described previously (38).…”
Section: Cloning Of the Mouse 11␤-hsd2 Promoter Region And Luciferasementioning
confidence: 99%
“…The test data for this purpose consisted of 21 developing mouse whole lung transcriptome profiles at six discrete time points: embryonic Days 14 (34), 17 (33), and 19 (34) and postnatal Days 7 (33), 14 (33), and 28 (34) (16,18). When projected in human lung development transcriptomic PC space, the mouse samples, especially the embryonic time points (14,17, and 19 dpc), were correlated with their true developmental age ( Figures 4B, E6, and E7).…”
Section: Estimating the Age/developmental Maturity Of The Human/ Mousmentioning
confidence: 99%
“…Depending on cell/tissue specificity, FOXM1 induces surfactant production by type II alveolar epithelial cells (31), increases differentiation of type I epithelial cells (32), regulates expression of tight junction proteins in endothelial cells (33,34), and increases macrophage recruitment after liver injury (35). Deletion of Foxm1 from embryonic lung epithelium causes respiratory failure after birth (31), whereas deletion of Foxm1 from alveolar type II cells of adult mice impairs alveolar barrier repair after acute lung injury (32). Although these studies demonstrated that FOXM1 is a critical transcriptional regulator of alveolar epithelial cells, the role of FOXM1 in the airway epithelium remains unknown.…”
mentioning
confidence: 99%